A influência do alcoolismo no equilíbrio postural - Giordani, Aline Marques (2004)
It is known that the alcoholism is a chronic disease that consists of an intoxication state caused by the consumption of alcohol. The signs and symptoms frequently found are among others: instability to walk, dizziness and psicomotoral descoordination. The objective of this study was to verify the influence of alcohol in the posture equilibrium. The sample consisted of 32 individuals for the experimental group, participants of Alcoholic Anonyms Group from Santa Maria-RS and 32 individuals who are not alcoholic for the control group. This research was developed at the Clinic of Otology of HUSM. All individuals were submitted to the otohrinolaryngologic evaluation, basic audiological, evaluation of the static and dynamic equilibrium and cerebelar tests, vecto-electronystagmography evaluation and dynamic posturography. Analyzing the results we could verify that the vecto-electronystagmography was normal in most of the individuals of the experimental group indicating that, in these individuals, the labyrinth and the vestibulo-oculomotorals vias would be normal and that the disturbance of the equilibrium presented by them would be a result of dysfunction in other areas of the central or outlying nervous system. Concerning to the evaluation with the dynamic posturography was verified that alcoholic abstainers present significant alterations of posture equilibrium when compared to individuals not alcoholic. Based on the analysis we can conclude that alcohol has harmful influence in the posture equilibrium.